2020
DOI: 10.5696/2156-9614-10.28.201208
|View full text |Cite
|
Sign up to set email alerts
|

Work Practices and Health Problems of Spray Painters Exposed to Organic Solvents in Ile-Ife, Nigeria

Abstract: Background. Automobile spray painters in Nigeria are exposed to organic solvents due to the hazardous nature of their work. Inadequate use of personal protective equipment (PPE) may intensify exposure to high levels of chemical hazards with resultant health problems. Objectives. The present study assessed PPE use and work practices and compared work-related health problems of spray painters and controls in Ile-Ife, Nigeria. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…Furthermore, there was a significant moderate negative correlation between FEV1, and FVC with both work experience and cumulative VOC exposure index. Several epidemiological studies have reported similar findings [10,[21][22][23], however, few studies conducted among organized sectors like shipyard and automobile industries have shown no differences in the PFT parameters such as FEV1 and FVC among painters compared to that of the matched unexposed individual [24,25]. A few of the contributing factors that might reduce the pulmonary functions in these unorganized sectors are inadequate health awareness, lack of usage of PPE, and non-adherence to safety measures and protocols by the employees and the employers of these sectors [26].…”
Section: Pulmonary Functions Among Paint Industry Workerssupporting
confidence: 65%
See 2 more Smart Citations
“…Furthermore, there was a significant moderate negative correlation between FEV1, and FVC with both work experience and cumulative VOC exposure index. Several epidemiological studies have reported similar findings [10,[21][22][23], however, few studies conducted among organized sectors like shipyard and automobile industries have shown no differences in the PFT parameters such as FEV1 and FVC among painters compared to that of the matched unexposed individual [24,25]. A few of the contributing factors that might reduce the pulmonary functions in these unorganized sectors are inadequate health awareness, lack of usage of PPE, and non-adherence to safety measures and protocols by the employees and the employers of these sectors [26].…”
Section: Pulmonary Functions Among Paint Industry Workerssupporting
confidence: 65%
“…The sample size was calculated using the formula n = Z21-α/2 PQ/L2, where Z = 1.96 [95% confidence interval (CI)] and P is the prevalence (P) of respiratory symptoms (wheezing: 7.5%) among spray painters exposed to volatile organic compounds and paint solvents in Nigeria [10], Q=1-P, and with a tolerable level of error (L) of 5% and the appropriate sample size (n=107) was derived.…”
Section: Sample Size Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…that are used in painting activities. Several investigations have indicated causal relationship between occupational exposure of painters to chemicals and its negative health outcomes, including increased DNA damage, genomic instability, and alterations in cellular kinetics. Exposure to emitted volatile chemicals from paint mixtures is a potential risk factor for developing respiratory illness among painters. Other suggested systemic health effects attributed to the exposure of paint chemicals are hematological, immunological, cardiovascular diseases, congenital malformations in offspring, and cancer. The International Agency for Research on Cancer (IARC) has classified “occupational exposure as a painter” is carcinogenic to humans (group 1)…”
Section: Introductionmentioning
confidence: 99%